Maranta Arundinacea Linn. (Tugaksheeri) – Phytochemical Evaluation - Viswan, Jeena P; Shincymol , V V; Ansary, P Y; Oommen, Sara Monsy (International Research Journal of Ayurveda & Yoga, 2022)
Tugaksheeri is an important drug that has been widely used in the preparation of various ayurvedic formulations. The plant is botanically identified as Maranta arundinacea Linn. of marantaceae family and has a nutrient dense starchy rhizome which has very low glycemic index, easy to digest and ideal for meeting the nutritional demands of sick. As per Samhithas and nighantusit is used in the treatment of kshaya (tuberculosis), swasa (dyspnoea), kasa (cough), daha (burning sensation), raktha dosha (disorders of blood), kamala (jaundice), pandu (anaemia) and mutrakruchra (dysuria). In folklore practices it is widely used in the treatment of diarrhea, dysentery and colitis. In order to validate these traditional claims scientifically and also to determine the quality and purity preliminary phytochemical evaluation of the drug was carried out. It revealed the presence of variable phytoconstituents such as alkaloids, phenol, flavonoids, steroid, carbohydrate etc which are responsible for the therapeutic potential of the drug. Values of total ash, acid insoluble ash, moisture content, alcohol and water-soluble extractives were comparable with the available references. Apart from the findings of previous research works, in the present study water insoluble ash value, quantitative estimation of fibre, tannin, total sugar, reducing sugar, qualitative analysis of ash for acid and basic radicals, successive solvent extraction in various solvents like petroleum ether, cyclohexane, acetone and alcohol, qualitative analysis of successive solvent extractives were carried out for the first time. All these findings will help to ensure the quality and purity of the drug.